2017
DOI: 10.5194/bg-14-3979-2017
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of community dynamics, temperature, and productivity on the hydrogen isotope signatures of lipid biomarkers

Abstract: Abstract. The hydrogen isotopic composition (δ 2 H) of lipid biomarkers has diverse applications in the fields of paleoclimatology, biogeochemistry, and microbial community dynamics. Large changes in hydrogen isotope fractionation have been observed among microbes with differing core metabolisms, while environmental factors including temperature and nutrient availability can affect isotope fractionation by photoautotrophs. Much effort has gone into studying these effects under laboratory conditions with single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…121! in central Switzerland were lower than those of brassicasterol in a nearby oligotrophic 122! lake (Ladd et al, 2017). There was, however, no significant difference in α Lipid-Water 123!…”
Section: Introduction 70!mentioning
confidence: 90%
See 3 more Smart Citations
“…121! in central Switzerland were lower than those of brassicasterol in a nearby oligotrophic 122! lake (Ladd et al, 2017). There was, however, no significant difference in α Lipid-Water 123!…”
Section: Introduction 70!mentioning
confidence: 90%
“…There was, however, no significant difference in α Lipid-Water 123! values for short-chain fatty acids and phytol between the two lakes (Ladd et al, 2017).…”
Section: Introduction 70!mentioning
confidence: 93%
See 2 more Smart Citations
“…However, such interspecies differences appear to be averaged 411 out in the soil as n-alkanes from soil samples did show a good correlation between wax C28 n-fatty acid reported from the sedimentary record of an Alpine lake may be due to 414 local factors such as length of growing season, amount of snowfall or anthropogenic 415 modification of the local vegetation (Wirth and Sessions, 2016), factors that are not always 416 well constrained. Ladd et al (2017) investigated the influence of growth rate and temperature 417 on the δ 2 H value of algal lipids (fatty acids and brassicasterol) in an oligotrophic and a 418 eutrophic lake. Although the authors found significant variability in the δ 2 H values of fatty acids 419 throughout the growing season the average δ 2 H value of the C16 n-fatty acid matched the δ 2 H 420 value of the lake water and was also preserved in the surface sediment.…”
Section: Molecule 255mentioning
confidence: 99%